Virtual Simulation of Plant Growth Towards Light - Kunsombat, Cherdsak (Agriculture and Natural Resources, 2014)
A plant growth simulation model was developed based on a diffusion-limited aggregation (DLA) model, which was modified by taking into account the influence of a light stimulus. The plant structure and the direction of growth were determined by adjusting the two parameters, α and θ, which control the strength and the direction of light, respectively. The simulation results showed that virtual plant growth can respond to the light source. The plant growth tended toward the light source in a designed direction between 60 and 120°.